Comparison of the 45-second/15-second intermittent running field test and the continuous treadmill test - Assadi, H.; Lepers, R. (International Journal of Sports Physiology and Performance, 2012)
Purposes: To compare the physiological responses and maximal aerobic running velocity (MAV) during an incremental intermittent (45-s run/15-s rest) field test (45-15) vs an incremental continuous treadmill test (TR) and to demonstrate that the MAV obtained during 45-15 (MAV) was relevant to elicit a high percentage of maximal oxygen uptake (VO) during a 30-s/30-s intermittent training session. Methods: Oxygen uptake (VO), heart rate (HR), and lactate concentration ([La]) were measured in 20 subjects during 2 maximal incremental tests and four 15-min intermittent tests. The time spent above 90% and 95% VO (t90% and t95% VO2max, respectively) was determined. Results: Maximal physiological parameters were similar during the 45-15FIT and TR tests (VO2max 58.6 ± 5.9 mL/kg·min for TR vs 58.5 ± 7.0 mL/kg·min for 45-15FIT; HRmax 200 ± 8 beats/min for TR vs 201 ± 7 beats/min for 45-15FIT). MAV45-15 was significantly (P < .001) greater than MAVTR (17.7 ± 1.1 vs 15.6 ± 1.4 km/h). t90% and t95% VO2max during the 30-s/30-s performed at MAVTR were significantly (P < .01) lower than during the 30-s/30-s performed at MAV45-15. Similar VO2 during intermittent tests performed at MAV45-15 and at MAVTR can be obtained by reducing the recovery time or using active recovery. Conclusions: The results suggested that the 45-15FIT is an accurate field test to determine VO2max and that MAV45-15 can be used during high-intensity intermittent training such as 30-s runs interspersed with 30-s rests (30-s/30-s) to elicit a high percentage of VO2max.